Banking Risk Management in the Light of Basel II - Vasile DEDU; Roxana NECHIF (Theoretical and Applied Economics, 2010)
This study presents a summary of what is the meaning of risk management in light of the Basel II Agreement. The study is structured in three parts, namely: credit risk management, significant credit risk management and credit risk management under Basel II Agreement. Thus, in the first part it refers to how developed the credit risk management over time and which are current phenomena that generate these risks, continuing in the second part with a summary of the reasons for which one wishes management of such credit risks, following the third party to talk about the shippings of Basel II in terms of credit risk management.